2019
DOI: 10.2174/1874210601913010301
|View full text |Cite
|
Sign up to set email alerts
|

Role of a Dentist in the Diagnosis of Child Abuse and Neglect: A Literature and Narrative Review

Abstract: Background: Child Abuse (CA) is defined as any physical or psychological harm inflicted upon children. The most commonly affected anatomical region in these cases is the orofacial complex, thereby placing dentists in a dominant position for detecting CA. The statistical figures referred to CA are high, and many cases go unreported. Objective: To determine the level of knowledge, the aptitudes and capacity of dentists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 55 publications
0
6
0
1
Order By: Relevance
“…35 Despite their key role mentioned at the beginning, reports of CAN by dentists are internationally rare. 25,36 A significant discrepancy between the number of suspicious cases and reported cases by dentists has been confirmed in studies worldwide. 20,22,24,37,38 The dentists surveyed, mainly justified their hesitation by knowledge deficits in diagnosis, 22,24,38 uncertainties in managing reporting pathways 15,[19][20][21] and fear of consequences for the practice or the child.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…35 Despite their key role mentioned at the beginning, reports of CAN by dentists are internationally rare. 25,36 A significant discrepancy between the number of suspicious cases and reported cases by dentists has been confirmed in studies worldwide. 20,22,24,37,38 The dentists surveyed, mainly justified their hesitation by knowledge deficits in diagnosis, 22,24,38 uncertainties in managing reporting pathways 15,[19][20][21] and fear of consequences for the practice or the child.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their key role mentioned at the beginning, reports of CAN by dentists are internationally rare 25,36 . A significant discrepancy between the number of suspicious cases and reported cases by dentists has been confirmed in studies worldwide 20,22,24,37,38 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that the main orofacial signs found were the presence of caries; increased dental plaque and gingival inflammation scores reflecting the close association between abuse and/or neglect and poor oral hygiene and heath. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%